On Execution of Maximum Current Protection in Distributive Network - F. A. Romaniuk; A. A. Tishechkin; N. N. Bobko; E. V. Glinsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper contains a brief analysis of protection devices applied for various elements of distributive networks with a single-way supply. Advantages and disadvantages of maximum current protection with current-temporary characteristics which are independent and inversely dependent on current and some new possible methods for improvement of current protection sensitivity of distributive networks are considered in the paper.